PENERAPAN PULSED ELECTROMAGNETIC THERAPY TERHADAP KEKUATAN OTOT PENDERITA STROKE DENGAN KELEMAHAN EXTREMITAS - Sutrisno Sutrisno; Widiyono Widiyono; Vitri Dyah Herawati (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2026)
Background: Stroke is a condition in which the body experiences neurological changes due to impaired blood flow to the brain. Stroke can cause long-term decline in body function due to muscle weakness and difficulty performing daily activities. Post-stroke patients require therapy and rehabilitation programs to restore functional abilities and avoid further complications. The purpose of this study was to examine the effect of pulsed electromagnetic therapy on muscle strength in post-stroke patients with limb weakness. Methods: This was a quasi-experimental study involving 28 respondents experiencing limb weakness due to stroke who were undergoing home care, divided into 18 intervention groups and 10 control groups. The study was conducted in September-October 2025. The sample selection method was purposive sampling. The instrument used to assess muscle strength was a manual muscle strength test. Data were tested using the Mann Whitney test. Researchers measured muscle strength in the upper extremities twice before and after the procedure, while in the control group it was assessed after 2 weeks without intervention. Results: There was no difference in muscle strength between the intervention and control groups before the procedure with a p-value of 0.42. After pulsed electromagnetic therapy was administered to the intervention group for 2 weeks, there was a difference in muscle strength between the intervention group and the control group with a p-value of 0.039. Conclusion: Regularly performing pulsed electromagnetic therapy can increase muscle strength in stroke patients experiencing limb weakness.